Sosialisasi Anti-Bullying melalui Teman Asik untuk Menciptakan Generasi Berkarakter Positif - Wulandari, Nindya; Muharram, Maulana; Yasmine, Amanda Alivio; Ardianti, Anggi; Bangun, Evelyn Theodora Br; Mahendwiani, Ihza; Silalahi, Hiskia Quintris Br; Maryanto, Luna Salwa Putri; Islami, Nurul Hidayah; Rahma, Puja Dwi; Auliya, Rizka; Raudah, Sya'rani (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying in elementary schools is a phenomenon that requires serious attention as it can affect students’ emotional, social, and academic development. Low levels of empathy, insufficient moral awareness, and differences in individual characteristics often contribute to the occurrence of bullying behavior. This community service program aimed to enhance students’ knowledge and awareness of the dangers of bullying through a participatory anti-bullying socialization activity entitled Teman Asik (Tanpa Ejekan Menumbuhkan Aksi Positif). The activity was conducted at SD Negeri 02 Kampung Dalam, Siak Regency, involving approximately 80 students from grades five and six. The implementation methods included interactive material delivery, discussions, educational games, video screenings, and reflective activities using an expression tree as a learning medium. The results indicated a high level of student participation and engagement throughout the socialization process. Students were able to understand various forms of bullying, recognize its negative impacts, and demonstrate increased confidence in expressing their opinions and feelings related to bullying. This activity plays an important role in fostering empathy, mutual respect, and collective awareness to create a safe and positive school environment.